2007
DOI: 10.1038/sj.onc.1210224
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein Sam68 contributes to proliferation and survival of human prostate cancer cells

Abstract: The tyrosine kinase Src is frequently activated in advanced human prostate carcinomas and its activation correlates with tyrosine phosphorylation of the RNAbinding protein Sam68. Herein, we have investigated the expression and function of Sam68 in human prostate cancer cells. Analysis of specimens obtained from 20 patients revealed that Sam68 is upregulated at the protein level in 35% of the samples. Real-time polymerase chain reaction confirmed the results at the mRNA level in most patients. Downregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(196 citation statements)
references
References 30 publications
9
187
0
Order By: Relevance
“…47,49,53 Previous data indicated that silencing of SND1 by small interfering RNAs (siRNAs) causes a significant decrease in PC3 cell growth. 43 As SAM68 was also shown to exert the same effect in the less-aggressive LNCaP cell line, 29 we first asked whether SND1 and SAM68 cooperate in supporting PCa cell proliferation. Transient knockdown of SND1 and SAM68 by RNAi in PC3 cells efficiently reduced the expression levels of both proteins at 48 h after transfection (Supplementary Figure S6A).…”
Section: Snd1 and Alternative Splicing M Cappellari Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…47,49,53 Previous data indicated that silencing of SND1 by small interfering RNAs (siRNAs) causes a significant decrease in PC3 cell growth. 43 As SAM68 was also shown to exert the same effect in the less-aggressive LNCaP cell line, 29 we first asked whether SND1 and SAM68 cooperate in supporting PCa cell proliferation. Transient knockdown of SND1 and SAM68 by RNAi in PC3 cells efficiently reduced the expression levels of both proteins at 48 h after transfection (Supplementary Figure S6A).…”
Section: Snd1 and Alternative Splicing M Cappellari Et Almentioning
confidence: 99%
“…Sequences for SAM68 siRNA were previously described. 29 The SND1 siRNA used was: 5 0 -UCUUUCUUCUGCUUUGCGG-3 0 . Scrambled siRNA was: 5 0 -GUGCUCAA UUGGAUUCUCU-3 0 .…”
Section: Sam68mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, acetylation of lysine residues by histone acetyltransferases enhances RNA binding (11). Finally, overexpression of Sam68 has been linked to prostate cancer, cell proliferation, and survival (12).…”
mentioning
confidence: 99%
“…(b) SAM68 KH-type RNA-binding proteins are intriguing molecules that regulate the differentiation and function of several cell types and influence tumour development (Busa et al 2007;. A well-studied member of this family, SAM68, is a ubiquitously expressed factor that regulates many steps of RNA metabolism, including alternative mRNA splicing, nuclear mRNA export and translation.…”
Section: Rna-binding Proteins That Regulate Spermatogenesismentioning
confidence: 99%